THE RELATIONSHIP BETWEEN FOOD PORTION SIZES AND ENERGY AND NUTRITIONAL INTAKE LEVELS AND NUTRITIONAL STATUS OF FEMALE STUDENTS IN AN ISLAMIC BOARDING SCHOOL IN SINGOSARI, MALANG REGENCY - Rayhanah, Salsabila Aurelia; Nurmayanti, Rani; Hapsari, Indri (Journal of Local Therapy, 2025)
Islamic boarding schools, as boarding institutions, are responsible for fulfilling the nutritional needs of their students, especially adolescent girls who require high intake for growth. Food portions that do not meet standards can cause energy and nutrient deficits, thus impacting nutritional status. This study aims to analyze food portion sizes, energy and nutrient consumption levels, nutritional status, and the relationship between variables in female students at one of the Islamic Boarding Schools in Singosari.. The study used a cross-sectional design with 41 respondents. Data were collected through weighing food portions for three days and 1x24-hour recalls, analyzed using the Spearman correlation test. The results showed that most staple food portions (51.2%), plant-based side dishes (78%), and all vegetable portions (100%) were insufficient. The level of energy consumption was classified as moderate deficit (36.6%), normal protein (39%), severe fat deficit (100%), normal carbohydrate (43.9%), and mild iron deficit (31.7%). Most students had normal nutritional status (90.2%). There was a significant relationship between staple food portions and energy and carbohydrate consumption levels, and plant-based side dish portions and protein consumption levels. As well as the level of energy, protein, and carbohydrate consumption with nutritional status (p<0.05).